2016
DOI: 10.1590/0034-7167.2016690422i
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de intervenções educativas na redução das complicações diabéticas: revisão sistemática

Abstract: RESUMO Objetivo: Apresentar as complicações neurocirúrgicas que ocorrem com grande freqüência; apesar dos esforços para preveni-las, algumas são inevitáveis. Método: Analisaram-se as principais complicações decorrentes de procedimentos neurocirúrgicos e os tratamentos específicos, baseados em revisão literária e em experiência própria. Conclusão: O tratamento médico dessas complicações pode ser transitório ou definitivo da causa subjacente, conforme a evolução clínica do paciente. PALAVRAS-CHAVE Neurocirurgia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
1
13
0
7
Order By: Relevance
“…The results of several systematic reviews support this finding [ 73 , 74 ]. Although many experts believe that the effectiveness of educational interventions alone is in doubt, it seems that training can be effective if it is targeted and accompanied by other interventions to change behavior [ 75 77 ]. The findings of this study showed that providing dairy products is one of the effective methods to increase dairy intake.…”
Section: Discussionmentioning
confidence: 99%
“…The results of several systematic reviews support this finding [ 73 , 74 ]. Although many experts believe that the effectiveness of educational interventions alone is in doubt, it seems that training can be effective if it is targeted and accompanied by other interventions to change behavior [ 75 77 ]. The findings of this study showed that providing dairy products is one of the effective methods to increase dairy intake.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 25% develop foot ulcers and 70% of all lower limb amputations are in people with DM, and 85% of surgical procedures are preceded by a foot ulcer (1)(2) . In this context, in recent years there has been a growing interest on the part of researchers and health professionals in the development of interventions for diabetic foot (DF) prevention and treatment (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review with meta-analysis found that on average an amputation costs between US$35,000 and US$45,000 in developed countries, and substantially less in developing countries at a cost of approximately US$5,000 (14) . Considering the high prevalence, complexity, severity and high costs of DF, systematic and educational interventions in prevention and treatment are mandatory (2)(3) .…”
Section: Introductionmentioning
confidence: 99%
“…Existem dois tipos de DM, conforme sua etiologia: o tipo 1, caracterizado pela deficiência na produção da insulina, decorrente da destruição autoimune das células β pancreáticas ou de natureza idiopática, que acomete principalmente crianças e adolescentes e é a forma menos comum da DM, com prevalência entre 5 a 10%. O DM tipo 2 é a mais predominante na população, correspondendo entre 90 a 95% e possui etiologia multifatorial, envolvendo aspectos ambientais e genéticos, e tem como característica a resistência à ação da insulina em conjunto com a perda progressiva de secreção da mesma 2,3 . O conceito de Qualidade de Vida (QV) está relacionado em diversos aspectos nos pacientes portadores de doenças crônicas, contribuindo positiva ou negativamente em seus tratamentos 4-6 . Devido às adversidades no enfrentamento da doença, o diabético pode ter sua QV prejudicada.…”
Section: Introductionunclassified